2018
DOI: 10.1021/acsami.8b16848
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic Magnetoelectric Coupling and Cotton–Mouton Effects in the Organic Magnetic Charge-Transfer Complex Pyrene–F4TCNQ

Abstract: Magnetoelectric coupling is of high current interest because of its potential applications in multiferroic memory devices. Although magnetoelectric coupling has been widely investigated in inorganic materials, such observations in organic materials are extremely rare. Here, we report our discovery that organic charge-transfer (CT) complex pyrene-2,3,5,6-tetrafluoro-7,7,8,8-tetracyanoquinodimethane (pyrene–F4TCNQ) can display anisotropic magnetoelectric coupling. Investigation of the crystal structure of pyrene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 39 publications
0
35
0
Order By: Relevance
“…Note that, recently, Yang et al. have found that the F 4 TCNQ‐based charge‐transfer complex can also afford a room temperature magnetoelectricity (Figure d) . Investigation shows that Pyrene–F 4 TCNQ has anisotropic magnetoelectric coupling with the coupling coefficient along the π–π stacking direction being much stronger than that along the other directions.…”
Section: Properties and Applicationsmentioning
confidence: 99%
“…Note that, recently, Yang et al. have found that the F 4 TCNQ‐based charge‐transfer complex can also afford a room temperature magnetoelectricity (Figure d) . Investigation shows that Pyrene–F 4 TCNQ has anisotropic magnetoelectric coupling with the coupling coefficient along the π–π stacking direction being much stronger than that along the other directions.…”
Section: Properties and Applicationsmentioning
confidence: 99%
“…Fundamentally, the dynamic and reversible nature of orthogonal hydrogen-bonding interactions is an intrinsic, original, and basic factor enabling these organized macromolecules to self-assemble into advanced supramolecular functional systems (Aida et al., 2012, Hoeben et al., 2005, Lehn, 2010, Sengupta and Würthner, 2013). Compared with the conventional superstructure with a range of common smart and mechanical properties, supramolecular conjugated solid states display a wide variety of complicated, photophysical mechanisms for electron delocalization, hybridization, and coupling (Heeger, 2010, Huang et al., 2019, Liu et al., 2017a, Liu et al., 2017b; Mikhnenko et al., 2015, Xie et al., 2012, Yang et al., 2018, Ye et al., 2018). Similar to the ordered, natural systems, the highly uniform and well-defined conjugated nanostructures that are receptive to processing can provide an effective and favorable electronic micro-environment that promotes exciton diffusion (Jin et al., 2018, Lin et al., 2010, Mikhnenko et al., 2015) and energy transport (Haedler et al., 2015, Kim et al., 2013, Vogelsang et al., 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, a new organic room-temperature CT multiferroic (mixed-stacking motif) based on F 4 TCNQ (2,3,5,6-tetrafluoro-7,7,8,8-tetracyanoquinodimethane, acceptor) and pyrene (donor) has been reported, which displayed anisotropic ME coupling effect and magneto-optical effect ( Figure 5). [36] In this system, compared to that with non-fluorinated acceptor (TCNQ), the fluorinated acceptor arouses an enhanced CT degree (causing closed-shell structure breaking), which indicates that more holes are generated on pyrene molecules (related to the spin polarization), thus leading to the enhanced spin density (magnetization). Besides, an anisotropic ME coupling behavior was observed, where the magnetization could be well tuned by an external electric field of different directions (horizontal and perpendicular direction) due to the anisotropy of molecular packing and CT interaction.…”
Section: Fluoride-based Ct Multiferroicsmentioning
confidence: 91%
“…However, some innovative and breakthrough researches have been obtained and significantly boosted the development of this field. [25,[27][28][29][30][31][32][33][34][35][36][37] Although many other systems such as polymers, [38a,b] covalent organic frameworks (COFs), [38c] or metal-organic frameworks (MOFs) [38d-f] have been demonstrated to show multiferroics properties, we only discuss recent progress in organic donor-acceptor cocrystals for multiferroic applications in this minireview. We begin with a brief description of multiferroics including the definition, history, evolution, significance, category and fundamental research to build a basic knowledge framework on the field, and then proceed with the presentation of the progress in experimental and theoretical investigations on organic CT multiferroics in the past decade.…”
Section: Introductionmentioning
confidence: 99%